1979
DOI: 10.1177/004051757904900101
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Warp and Filling Variables on the Tensile Failure and Joint Strength of Kevlar® 29 Parachute .Webbing

Abstract: The effect of filling and warp yarn variables on the strength of a nominally designated 60 kN, 2.9 cm Kevlar® 29 parachute webbing was investigated. The goal was to increase webbing and jointed webbing strength without in creasing the weight of the structure. Webbing of varying pick spacing, filling yarn strength, and amount of warp yarn twist was fabricated and tested at quasi-static and high strain rates. Improved strength was obtained when: a the filling was reduced from two to single-ply yarn, b) pick … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Optimum fabric strength is predicted to occur at warp yarn twist levels lower than those predicted from conventional yarn data.. ; ,, 4. Results of the simulation tests correlate generally, with trends observed in woven structures in constructions where the warp yarns are compressed…”
Section: Mplications Of Simulation Results In Warpmentioning
confidence: 66%
“…Optimum fabric strength is predicted to occur at warp yarn twist levels lower than those predicted from conventional yarn data.. ; ,, 4. Results of the simulation tests correlate generally, with trends observed in woven structures in constructions where the warp yarns are compressed…”
Section: Mplications Of Simulation Results In Warpmentioning
confidence: 66%
“…It has been shown that increased warp yarn crimp reduces the strength of woven Kevlar structures. 9 The latter result was obtained by altering the pick spacing in woven structures. In the case of a 60 kN webbing, a change in pick spacing from 4 to 6.picks/cm lowered the strength from 70 to 63 kN.…”
Section: Yarn Swellingmentioning
confidence: 99%
“…In the case of a 60 kN webbing, a change in pick spacing from 4 to 6.picks/cm lowered the strength from 70 to 63 kN. 9 By calculating changes in yarn geometry using typical geometric values for the appropriate Kevlar webbing and based on a 4% moisture absorption, 4 it was concluded that fiber swelling was an unlikely mechanism for the observed degradation.…”
Section: Yarn Swellingmentioning
confidence: 99%
“…Of the very few studies on webbings in parachute assemblies [10,11], Ericksen et al [10] evaluated the effect of warp and weft variables on the strength of joints in Kevlar webbings. Onal [11] studied the mechanical properties of notched webbings in cluster sub-munition parachutes.…”
mentioning
confidence: 99%